Heterotopic Pregnancy Following Intrauterine Insemination: A Case Report - Balcı, Osman; Karataylı, Rengin; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2007)
A 30 years old patient admitted to our clinic with severe pelvic pain and vaginal bleeding. In history, it was also learned that she had been pregnant for triple gestation after intrauterine insemination. She was advanced anemic by inspection. Patient was evaluated by transvaginal ultrasonography, there were three gestational sacs and fetuses with fetal heart movements and CRL values correlated with 10th week of gestation within the uterine cavity. Left adnexal area was normal, but there was an ectopic gestational sac and fetal echo on the right tuba-ampullary region. There was also hematoma adjacent to the ectopic focus and large amounts of fluid within the abdominal cavity. Laparotomy was planned. Salpingotomy was performed, and ectopic focus was taken out. On the postoperative 3rd day, since patient was stabilized, she was discharged from hospital. Triple gestation is still being followed-up at 20 weeks without any problem.